Pertanggungjawaban Pidana terhadap Pelaku Tindak Pidana Perdagangan Orang - Gaib, Brigita Misrawati; Lolong, Wenly R. J.; Simandjuntak, Reynold (Universitas Batanghari Jambi, 2026)
This study aims to discussone type of crime, namely human trafficking. This study uses a normative juridical research method, using literature analysis and secondary datacovering primary legal materials, secondary legal materials, and tertiary legal materials. The results of this studyshow that the Human Trafficking Law provides astrong legal basis. It explicitly formulates various elements of the crime ofhuman trafficking along with severe criminal sanctions. Criminal liability is not only given to the main perpetrator butalso to those who participate in the crime. However, one issue that often poses a challenge is the lack of in-depth understandingby law enforcement officials regarding the nature and complexity of the crime ofhuman trafficking. Therefore, continuous training forlaw enforcement officials and technical capacity building for investigators in maximizing the use ofthe articles on the crime of human trafficking are needed.